Endoscopic Management of Benign Biliary Strictures After Liver Transplantation. Issue 2 (31st January 2019) - Larghi, Alberto; Tringali, Andrea; Rimbaş, Mihai; Barbaro, Federico; Perri, Vincenzo; Rizzatti, Gianenrico; Gasbarrini, Antonio; Costamagna, Guido
Abstract : Biliary strictures represent some of the most frequent complications encountered after orthotopic liver transplantation. They comprise an array of biliary abnormalities with variations in anatomical location, clinical presentation, and different pathogenesis. Magnetic resonance cholangiography represents the most accurate noninvasive imaging test that can provide detailed imaging of the whole biliary system—below and above the anastomosis. It is of particular value in those harboring complex hilar or intrahepatic strictures, offering a detailed roadmap for planning therapeutic procedures. Endoscopic therapy of biliary strictures usually requires biliary sphincterotomy plus balloon dilation and stent placement. However, endoscopic management of nonanastomotic biliary strictures is much more complex and challenging as compared with anastomotic biliary strictures. The present article is a narrative review presenting the results of endoscopic treatment of biliary strictures occurring after liver transplantation, describing the different strategies based on the nature of the stricture and summarizing their outcomes.